The Influence of Social Media Interaction and Reproductive Health Knowledge on Risky Sexual Behavior Among Adolescents - Belgis Nikmatul Azza; Lilik Djuari; Endyka Erye Frety (JUKEJ : Jurnal Kesehatan Jompa, 2026)
Social media plays a pivotal role in shaping adolescents' reproductive health knowledge and sexual behavior by providing broad access to health information while simultaneously exposing users to misinformation that may increase risky sexual practices. This study aimed to examine the relationship between social media interaction, reproductive health knowledge, and risky sexual behavior among adolescents. A quantitative study with a cross-sectional design was conducted involving 335 respondents selected using probability sampling with a purposive sampling approach. Data were collected through a structured questionnaire. The independent variables were social media interaction and reproductive health knowledge, while the dependent variable was risky sexual behavior. Data were analyzed using Spearman's rho correlation test with a significance level of p < 0.05. The results indicated a significant relationship between social media interaction and risky sexual behavior (p = 0.000; r = −0.230), although the correlation strength was weak. Reproductive health knowledge was also significantly associated with risky sexual behavior (p = 0.048; r = −0.106), demonstrating a similarly weak negative correlation. These findings suggest that both social media interaction and reproductive health knowledge are significantly associated with risky sexual behavior among adolescents, although the magnitude of these relationships remains relatively weak. Strengthening digital health literacy and comprehensive reproductive health education is essential to promote healthier sexual decision-making among adolescents.